Estimation and Tracking for Millimeter Wave MIMO Systems Under Phase Noise Problem - Faragallah, Osama S.; El-Sayed, Hala S.; El-Mashed, Mohamed G. (IEEE access, 2020)
Millimeter wave (mmWave) system is a key technology for the fifth generation (5G). Precoding techniques can be applied in the radio frequency (RF) stage to achieve spatial multiplexing gain. Studying the problems of hardware imperfections in the RF stage for mmWave communication system is very important because it can affect the transmitted signals and overall system performance. In this article, mmWave MIMO system under phase noise problem is proposed. In addition, an optimization problem for the design of hybrid precoder under phase noise is formulated. An alternating minimization algorithm using manifold optimization is proposed to close the performance of the fully digital precoder. A realistic power consumption model is considered. To estimate the mmWave channel parameters and to track the phase noise parameters, a Bayesian Cramér-Rao lower bounds (BCRLBs), Kalman filter, least square (LS) and maximum a posterior (MAP) algorithms are proposed. Furthermore, the proposed system with ideal hardware mmWave system is compared with non-ideal system under amplified thermal noise and residual additive transceiver hardware impairments. Spectral efficiencies (SEs) of the proposed system are provided with different scenarios. The analytical and simulation tests show that the influence of phase noise problem may decrease SE performance, especially at higher phase noise.